2022
DOI: 10.1002/cphc.202200685
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Transfer from an Innately Chiral Nanocrystal Core to a Nematic Liquid Crystal 2: Lyotropic Chromonic Liquid Crystals

Abstract: The importance of and the difference between molecular versus structural core chirality of substances that form nanomaterials, and their ability to transmit and amplify their chirality to and within a surrounding condensed medium is yet to be exactly understood. Here we demonstrate that neat as well as disodium cromoglycate (DSCG) surface‐modified cellulose nanocrystals (CNCs) with both molecular and morphological core chirality can induce homochirality in racemic nematic lyotropic chromonic liquid crystal ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…CNC themselves can export chirality to a materially foreign nematic liquid crystalline phase, for instance authors in refs [206][207] , utilising a hydrophobic nematic liquid crystalline host as a reporter, recently confirmed that clean and chemically (hydrophobic) altered CNCs may convey chirality over space. To boost their chirality transfer effectiveness in comparison to plain CNCs or even CNCs functionalized with chiral molecules, these modified CNCs had their surfaces functionalized with achiral molecules that were chemically linked to the hydrophobic nematic liquid crystalline host.…”
Section: Origin Of Chiralitymentioning
confidence: 97%
“…CNC themselves can export chirality to a materially foreign nematic liquid crystalline phase, for instance authors in refs [206][207] , utilising a hydrophobic nematic liquid crystalline host as a reporter, recently confirmed that clean and chemically (hydrophobic) altered CNCs may convey chirality over space. To boost their chirality transfer effectiveness in comparison to plain CNCs or even CNCs functionalized with chiral molecules, these modified CNCs had their surfaces functionalized with achiral molecules that were chemically linked to the hydrophobic nematic liquid crystalline host.…”
Section: Origin Of Chiralitymentioning
confidence: 97%
“…To elucidate the role of core chirality, we recently reported on the chirality transfer by nanostructures with an intrinsically chiral core, i.e., cellulose nanocrystals (CNCs) that were further covalently modified with either chiral or achiral molecules. 16,17 We found that among such CNCs, those functionalized with achiral moieties structurally related to the N-LC showed better N-LC solubility and thus serving as efficient chiral inducers with b w values from À35 mm À1 for neat to À54 mm À1 for cholesterol-modified CNCs. Here, functionalization with chiral molecules rather than just mesogenic moieties that were structurally alike to the N-LC host only slightly enhanced the efficacy of helical distortion in the host N-LC, indicating the high propensity of CNCs to transfer chirality from an inherently chiral core.…”
Section: Introductionmentioning
confidence: 93%
“…, cellulose nanocrystals (CNCs) that were further covalently modified with either chiral or achiral molecules. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…While cholesteric and nematic mesophases have been reported from the self-assembly of CNCs grafted with LC of similar orientational order, smectic mesophases have been reported from the self-assembly of CNCs grafted with LCs of diverging orientational order during self-assembly, as described below. 7,11,46 2.1.1. Click Chemistry.…”
Section: Modification Of Cellulose Nanocrystals With Liquid Crystalli...mentioning
confidence: 99%
“…Selection of LCs or LCPs that have diverging orientational order from CNCs will enable technologies that cannot be obtained from the conventional N* mesophase of CNCs. While cholesteric and nematic mesophases have been reported from the self-assembly of CNCs grafted with LC of similar orientational order, smectic mesophases have been reported from the self-assembly of CNCs grafted with LCs of diverging orientational order during self-assembly, as described below. ,, …”
Section: Modification Of Cellulose Nanocrystals With Liquid Crystalli...mentioning
confidence: 99%